Identifying the determinants of the performant use of dashboards in Moroccan companies facing the digitization challenges - Alami, Mohamed (Eastern-European Journal of Enterprise Technologies, 2025)
The digitalization movements are causing profound changes affecting organizational structures and managerial practices in companies, particularly following the collapse of the performance control paradigm and the emergence of its piloting through various tools, with dashboards being the most commonly used. The aim of this study is to identify the determinants of the performant use of dashboards by managers throughout the performance piloting process, in order to overcome the challenges imposed by the digitalization of their economic and social environment. The results reveal that some companies succeed in their digital transition and in maximizing the value of digital dashboards, while others face delays hindering this goal. This leads to the identification of three key determinants for the performant use of dashboards. These are, the necessity of adopting information technologies that integrate all processes which is highly correlated (r>0.62) with the degree of total integration and complete automation of dashboards, the obligation to develop a favorable behavior towards the use of information technologies which presents a high correlation (r=0.764146) with managers’ excessive use of digitized dashboards, and the importance of adopting flexible structures to reduce decision-making constraints for managers with an important correlation (r=0.673879) with the large use of digitized dashboards. A distinctive feature of these results is that they show a comparison between highly digitized companies and those in the initial phase of digitization. This would enable the latter to manage their digital transition well, by making it easier for their managers to pilot their activities, with a view to obtaining organizational and competitive advantages, provided that throughout the digitalization process they adopt restructuring policies based on the modernization of their structures and the integration of informatics culture into their strategies, in order to develop the piloting competencies of their managers and to deal with unfavorable attitudes towards the use of digital technologies